Chemically initiated liquid-like behavior and fabrication of periodic wavy Cu/CuAu nanocables with enhanced catalytic properties. Issue 19 (2nd May 2018) - Jiang, Zhiyuan; Jiang, Qiaorong; Huang, Rao; Sun, Mingjun; Wang, Kaili; Kuang, Qin; Zhu, Zi-Zhong; Xie, Zhaoxiong
Abstract : Chemical processes may play a similar role as heat and initiate liquid-like behavior of crystalline Cu/CuAu nanocables at a temperature far below their melting points. Abstract : Solid crystalline materials have long range order in their atomic arrangement while liquids have short range order, and the transition between them is usually caused by heat and/or pressure. Herein, we report the finding that chemical processes may play a similar role as heat and initiate liquid-like behavior of crystalline nanomaterials at a temperature far below their melting points. When the straight Cu/CuAu crystalline nanocables are dispersed in organic amine at 80 °C under ambient conditions, the continuous oxidation of Cu atoms on the surface and diffusion of Cu atoms from the core to the surface would break up the long-range ordered arrangement of atoms and lead to the transformation of an anisotropic crystal into an isotropic liquid-like state, which resulted in the evolution of the straight morphology of the nanocables into periodic wavy structures following the Rayleigh instability. It was also demonstrated that periodic wavy Cu@CuAu nanocables exhibit much better catalytic activity than straight Cu@CuAu nanocables towards the reduction of p -nitrophenol into p -aminophenol by NaBH4 . Our results not only provide new insights into the transition between a solid crystal and a liquid-like state at the nanoscale, but also facilitate the development of new strategies for the synthesis of functional nanomaterials.